Ответ:
4 107/126
Пошаговое объяснение:
если я правильно поняла уравнение, то вот ответ↑
(х - 3 5/18) * 3 1/2 = 5 1/2
х - 3 5/18 = 5 1/2 : 3 1/2
х - 3 5/18 = 11/2 : 7/2
х - 3 5/18 = 11/2 * 2/7
х - 3 5/18 = 11/7
х - 3 5/18 = 1 4/7
х = 1 4/7 + 3 5/18
х = 1 72/126 + 3 35/126
х = 4 107/126
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
4 107/126
Пошаговое объяснение:
если я правильно поняла уравнение, то вот ответ↑
Ответ:
Пошаговое объяснение:
(х - 3 5/18) * 3 1/2 = 5 1/2
х - 3 5/18 = 5 1/2 : 3 1/2
х - 3 5/18 = 11/2 : 7/2
х - 3 5/18 = 11/2 * 2/7
х - 3 5/18 = 11/7
х - 3 5/18 = 1 4/7
х = 1 4/7 + 3 5/18
х = 1 72/126 + 3 35/126
х = 4 107/126